Anti-Progesterone in Environmental Water - Elise Rose; Michael Varveris (Issues in Law & Medicine, 2026)
Past research has shown that steroid hormones and other endocrine-disrupting compounds (EDCs) are present in environmental water, with implications for human and wildlife health. Abortion providers have shifted a large part of their practice to medication-induced abortion, using the anti-progesterone synthetic steroid hormone mifepristone. We wanted to see if mifepristone, an EDC, could be detected in water sources. Water samples were collected from sites upstream and downstream of water treatment facilities and from municipal tap water in each of 3 American cities. The water samples were tested for mifepristone using the PR CALUX® assay. There were significant levels of anti-progesterone activity (up to 0.041 μgram/l) in the water of all but one of the nine sampling classes. Given progesterone's numerous effects, this contaminant could affect the physiology of aquatic animals and human health, including fertility, pregnancy, and fetal development. The findings indicate the significant need for additional investigation into the levels of various hormones and EDCs, including mifepristone, in water sources.